Integrated Hazard-Vulnerability-Risk Analysis and Landslide Zonation Mapping in Chamoli District: A Geospatial Approach - Bhattacharya, Uma; Jolly, Dr. Rajesh (International Journal of Aquatic Research and Environmental Studies, 2026)
The study is an in-depth analysis of hazards, vulnerability, and risk in disaster management, with a particular focus on the Chamoli district in the Uttarakhand, Central Himalaya. Hazards have been defined by origin, speed of onset, frequency, and spatial characteristics, illustrating how these events transform into disasters when interacting with vulnerable conditions. Vulnerability is thoroughly examined through its components— susceptibility and resilience—and categorized by their physical and environmental dimensions, based on the existing geographical indicators. Furthermore, this study explores risk as the expected loss resulting from the interaction of hazard and vulnerability. A significant portion of the sources then applies these concepts to landslide hazard zonation mapping in Chamoli, integrating geospatial analysis, geological settings, and structural features to assess regional stability for infrastructural development, such as road construction, while considering the area's seismic vulnerability and environmental challenges.
Keywords: Hazards, Vulnerability, ASTER DEM, Landslide-zonation